Життєвий цикл фірми: фактори і напрями впливу - Лукашова, С. В. (Видавництво Національного університету «Львівська політехніка», 2001)
Розглянуто поняття життєвого циклу фірми (ЖЦФ). Висвітлено роль управління ЖЦФ у ринковій стійкості сучасних підприємств. Наведено основний зміст зусиль щодо напрямів функціонування фірми на окремих стадіях ЖЦФ. Проаналізовано фактори впливу на ЖЦФ. Розкрито тенденції диверсифікації товарної політики. The definition of the life-cycle of the firm is considered in the article. The role of management of the life-cycle in the market stableness of the modern enterprises is studied. The basic the efforts due to the tendency of the functionning of the firm of the particular level of the life-cycle are given. The analysis of the factors that influence the life-cycle is made. The tendency of the diversification of the product policy was developed.